2014
DOI: 10.1152/ajpendo.00489.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of adiponectin in the metabolic effects of cannabinoid type 1 receptor blockade in mice with diet-induced obesity

Abstract: The adipocyte-derived hormone adiponectin promotes fatty acid oxidation and improves insulin sensitivity and thus plays a key role in the regulation of lipid and glucose metabolism and energy homeostasis. Chronic cannabinoid type 1 (CB1) receptor blockade also increases lipid oxidation and improves insulin sensitivity in obese individuals or animals, resulting in reduced cardiometabolic risk. Chronic CB1 blockade reverses the obesity-related decline in serum adiponectin levels, which has been proposed to accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 80 publications
3
38
0
Order By: Relevance
“…RIM, however, restored SCAD, MCAD, and LCAD levels to those of the Prefat period. Thus, our results are consistent with other studies (13,49) showing that RIM increased fatty acid oxidation in a fat-fed model of insulin resistance. The anti-inflammatory property of adiponectin has been extensively studied in the past decade (38).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…RIM, however, restored SCAD, MCAD, and LCAD levels to those of the Prefat period. Thus, our results are consistent with other studies (13,49) showing that RIM increased fatty acid oxidation in a fat-fed model of insulin resistance. The anti-inflammatory property of adiponectin has been extensively studied in the past decade (38).…”
Section: Discussionsupporting
confidence: 93%
“…FAS gene expression demonstrated the same tendency. These results are consistent with other studies showing that reversal of HFD-induced hepatic steatosis and fibrosis by RIM requires adiponectin (49). Although this study demonstrated that some hepatoprotective effects of RIM such as improvement of hepatic steatosis and fatty acid oxidation are adiponectin dependent, other metabolic effects, such as decreased improvement of hepatic insulin resistance by RIM, are independent of adiponectin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…), and diet‐induced obese mice (Tam et al. ). Similarly, dyslipidemia in the form of elevated triglycerides is reported in (mRen2)27 rats and may contribute to defective insulin signaling in this strain (Sloniger et al.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these compounds on intestinal lipid absorption remains to be elucidated. Rimonabant enhances FA oxidation in WAT 72 and liver, 73 which could be partly responsible for the lipidlowering effect of rimonabant.…”
Section: Bat Activation and Browning As A Tool To Alleviate Hypertrigmentioning
confidence: 99%